The recovered life of Isaac Anderson - Jackson, Alicia K. (University Press of Mississippi, 2021)
"Owned by his father, Isaac Harold Anderson (1835-1906) was born enslaved but went on to become a wealthy businessman, grocer, politician, publisher, and religious leader in the African American community in the state of Georgia. Elected to the state senate, Anderson replaced his white father there, and later shepherded his people as a founding member and leader of the Colored Methodist Episcopal church. He helped support the establishment of Lane College in Jackson, Tennessee, and helped freed people leave Georgia for safe havens in northern Mississippi and Arkansas. Eventually under threat to his life, Anderson fled to Arkansas, and then later still, to Holly Springs, Mississippi. Much of Anderson's unique story has been lost to history-until now. In The Recovered Life of Isaac Anderson, author Alicia K. Jackson presents a biography of Anderson and in it a microhistory of Black religious life and politics after emancipation. A work of recovery, the volume captures the life of a shepherd to his journeying people, and of a college pioneer, a CME minister, a politician, and a freed person"--